2012
DOI: 10.1155/2012/196715
|View full text |Cite
|
Sign up to set email alerts
|

The SARAH Domain of RASSF1A and Its Tumor Suppressor Function

Abstract: The Ras association domain family 1A (RASSF1A) tumor suppressor encodes a Sav-RASSF-Hpo domain (SARAH), which is an interaction domain characterized by hWW45 (dSAV) and MST1/2 (dHpo). In our study, the interaction between RASSF1A and RASSF1C with MST1 and MST2 was demonstrated and it was shown that this interaction depends on the SARAH domain. SARAH domain-deleted RASSF1A had a similar growth-reducing effect as full-length RASSF1A and inhibited anchorage independent growth of the lung cancer cell lines A549 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Nuclear actin is exported from the nucleus by XPO6, independently of the general export receptor CRM1, and it is imported by IPO9 (Stuven et al, 2003;Dopie et al, 2012). Intriguingly, the RASSF1A/ RAN/XPO6 complex includes MST2, suggesting that the recruitment of RASSF1A to MST2 at the NE potentially supports XPO6 binding via the SARAH domain (Dittfeld et al, 2012) and this is important for the active participation in actin-profilin nucleocytoplasmic shuttling. We found that lack of RASSF1A, a phenomenon commonly observed in human tumours, leads to accumulation of actin within the nucleus due to defective nuclear export.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear actin is exported from the nucleus by XPO6, independently of the general export receptor CRM1, and it is imported by IPO9 (Stuven et al, 2003;Dopie et al, 2012). Intriguingly, the RASSF1A/ RAN/XPO6 complex includes MST2, suggesting that the recruitment of RASSF1A to MST2 at the NE potentially supports XPO6 binding via the SARAH domain (Dittfeld et al, 2012) and this is important for the active participation in actin-profilin nucleocytoplasmic shuttling. We found that lack of RASSF1A, a phenomenon commonly observed in human tumours, leads to accumulation of actin within the nucleus due to defective nuclear export.…”
Section: Discussionmentioning
confidence: 99%
“…The process of signal transduction involves the formation of MST2 dimers, and the dimerization process is governed by the interaction through SARAH domains [12,19,[29][30][31][32] ( Figure 3A). In addition, RASSF scaffolds also interact with and regulate the activity of MST proteins through protein interactions mediated by their SARAH domain ( Figure 3B).…”
Section: Sarah Domainsmentioning
confidence: 99%
“…For example, interactions between RASSF1A (and RASSF1C) and MST1 and MST2 have been identified and analyzed showing that this interaction depends on the C-terminal SARAH domain, i.e. dimerization of both SARAH domains of each protein [31]. Nevertheless, few crystal structures are available for heterodimers, i.e.…”
Section: Sarah-sarah Domain Interactionsmentioning
confidence: 99%
“…Studies show that the RASSF1A gene rarely mutates, and its low or loss of expression is mainly due to hypermethylation of the CpG island in the promoter region 8 . RASSF1A can be used as a negative upstream regulator of YAP [9][10][11] , which may play an important role in psoriasis pathogenesis. However, its expression and mechanism in psoriasis are still unclear.…”
Section: Introductionmentioning
confidence: 99%